Relevance as Social Matrix of Attention in Alfred Schutz - Campo, Enrico (SocietàMutamentoPolitica, 2016)
Attention is a critical faculty in contemporary Western societies. What is surprising is the fact that attention has been mainly analyzed as an individual phenomenon. Scientific research that treats attention exclusively on the individual level simplifies an enormously complex situation. Instead, according to the idea defended in this essay, one cannot think of attention and perception without regard for cultural conventions and social norms. This article therefore proposes to investigate attention precisely in its social dimension. In particular, the specific objective is to highlight the contribution Alfred Schutz’s theory of systems of relevance can give to the understanding of the social mechanisms that regulate attention. In order to demonstrate the viability of the Schutzian proposal, here are discussed some recent perspectives that explore the mechanisms of the social regulation of attention. The article will briefly revisit these contributions that explicitly investigate intersubjective and collective attention, and will focus especially on the proposals of Eviatar Zerubavel and Yves Citton. Then is analyzed the role of attention in the theoretical edifice of Schutz, to focus on the relationship between attention and systems of relevance.